Properties of hybrid TiN/Al₂O₃ coatings using electron beam melting - Kylyshkanov, M.K. (Физическая инженерия поверхности, 2007)
New experimental results on studies of the structure, element and phase composition of hybrid coatings deposited on a substrate of stainless steel AISI 321 are presented using combined application of several methods of coating deposition (plasma-detonation and vacuum arc ones) with subsequent surface treatment by a high-current electron beam (HCEB). We found that an increase in the energy density enhanced the processes of mass-transfer and allowed one to produce denser powder coatings. We demonstrated the results of corrosion tests for TiN/Al₂O₃ coatings in their initial state and after electron-beam modification of their surfaces. We obtained an essential increase in the hybrid coating resistance to corrosion in 0.5 M solution of H₂SO₄ after electron beam treatment.